Targeting CD73 with flavonoids inhibits cancer stem cells and increases lymphocyte infiltration in a triple-negative breast cancer mouse model - Mediratta, Karan; El-Sahli, Sara; Marotel, Marie; Awan, Muhammad Z.; Kirkby, Melanie; Salkini, Ammar; Kurdieh, Reem; Abdisalam, Salman; Shrestha, Amit; Di Censo, Chiara; Sulaiman, Andrew; McGarry, Sarah; et al. (Frontiers in Immunology, 2024)
Chemotherapy remains the mainstay treatment for triple-negative breast cancer (TNBC) due to the lack of specific targets. Given a modest response of immune checkpoint inhibitors in TNBC patients, improving immunotherapy is an urgent and crucial task in this field. CD73 has emerged as a novel immunotherapeutic target, given its elevated expression on tumor, stromal, and specific immune cells, and its established role in inhibiting anti-cancer immunity. CD73-generated adenosine suppresses immunity by attenuating tumor-infiltrating T-and NK-cell activation, while amplifying regulatory T cell activation.Chemotherapy often leads to increased CD73 expression and activity, further suppressing anti-tumor immunity. While debulking the tumor mass, chemotherapy also enriches heterogenous cancer stem cells (CSC), potentially leading to tumor relapse. Therefore, drugs targeting both CD73, and CSCs hold promise for enhancing chemotherapy efficacy, overcoming treatment resistance, and improving clinical outcomes. However, safe and effective inhibitors of CD73 have not been developed as of now. In our study, we examined the impact of natural flavonoids quercetin and luteolin, which are commonly used as over-the-counter supplements. When quercetin and luteolin were combined with the chemotherapeutic paclitaxel in a triple-drug regimen, we found an effective downregulation in paclitaxel-enhanced CD73 and CSC-promoting pathways YAP and Wnt. We found that CD73 expression was required for the maintenance of CD44 high CD24 low CSCs, and co-targeting CD73, YAP, and Wnt effectively suppressed the growth of human TNBC cell lines and patient-derived xenograft organotypic cultures. Furthermore, triple-drug combination inhibited paclitaxel-enriched CSCs and simultaneously improved lymphocyte infiltration in syngeneic TNBC mouse tumors. Conclusively, our findings elucidate the significance of CSCs in impairing anti-tumor immunity. The high efficacy of our triple-drug regimen in clinically relevant platforms not only underscores the importance for further mechanistic investigations but also paves the way for potential development of new, safe, and cost-effective therapeutic strategies for TNBC.